Turkey : a past against history - Philliou, Christine May (University of California Press, 2021)
"From its earliest days, the dominant history of the Turkish Republic was told as a triumphant narrative of national self-determination and secular democratic modernization. In that officially sanctioned account, the years between the fall of the Ottoman Empire and the formation of the Turkish state marked an absolute rupture, and the Turkish nation formed an absolute unity. In recent years, this hermetic division has begun to erode-but as the old consensus collapses, new histories and accounts of political authority have been slow to take its place. In this richly detailed alternative history of Turkey, Christine M. Philliou focuses on the notion of political opposition and dissent-muhalefet-to weave together the Ottoman and Turkish periods. Taking the perennial dissident Refik Halid Karay (1888-1965) as a subject, guide, and interlocutor, she traces the fissures within the Ottoman and the modern Turkish elite that bridged the Ottoman Empire and Republican Turkey. Exploring Karay's political and literary writings across four regimes and two stints in exile, along with his direct confrontation with Mustafa Kemal Atatürk at a crucial moment in 1919, Philliou upends the official history of Turkey and offers new dimensions to our understanding of its political authority and culture"--